(untitled) (Journal of actual problems of jurisprudence, 2018)
The present paper outlines the characteristics of social rights as types of constitutional rights. The conditions and procedures for exercise of social human rights can vary depending on economic system condition of the state and social services development. Social rights of the person and of the citizen are an integral part of the rights and liberties guaranteed by the Constitution, enforcement of which is the main function of the state. Key words: social rights, social safeguard, social protection, social function of the state. Key wods: social rights, social safeguard, social protection, social function, of the state.